383 TAKOTSUBO SYNDROME AFTER CAR-T CELL INFUSION. (15th December 2022) - Bastianoni, Gianmarco; Brugiatelli, Leonardo; Selimi, Adelina; Stronati, Giulia; Paolini, Federico; Alfieri, Michele; Belleggia, Sara; Torselletti, Lorenzo; Coraducci, Francesca; Coretti, Francesca; Principi, Samuele; Frangione, Alice; et al.
Abstract: Introduction: The mechanisms of cardiotoxicity during CAR-T cell therapy remain unclear to this day. We present the case of a 63-year-old woman with diffuse large B-cell lymphoma, who underwent CAR-T cell therapy. Five days after the infusion, she developed takotsubo cardiomyopathy. This is one of the rare cases of CAR-T cell-induced takotsubo cardiomyopathy. Case Description: a 63-year-old woman with a diffuse large B-cell lymphoma and without significant cardiovascular history was treated with CAR-T cell therapy. The patient had arterial hypertension, dyslipidemia and history of CAD in the family. Prior to CAR-T cell therapy, she underwent baseline cardiac evaluation with an echocardiogram which showed a normal biventricular function. Within 24 hours of the infusion of CAR-T cells, she developed grade I cytokine release syndrome (CRS) with high-grade fever and sinus tachycardia. On day four, she developed grade three immune effector cell associated neurological syndrome which was treated with tocilizumab and dexamethasone. On day five laboratory testing showed a disproportionate elevation of BNP compared to hs-TnI. An ECG reported diffuse new-onset T wave inversion in all the precordial leads and a prolonged QT interval, and an echocardiogram showed severely reduced left ventricular ejection fraction (EF = 30%) with evidence of apical ballooning and right ventricular systolic dysfunction. Coronary angiography showed significant stenosis of the middle segment of the circumflex artery, which poorly could explain the clinical presentation of the patient. Ventriculography was also performed, which confirmed the ultrasound findings. During the next 48 hours, ECG and left ventricular function improved along with a gradual reduction of BNP and hs-TnI. We concluded that takotsubo syndrome was the most likely diagnosis. The InterTAK score was 89, which corresponded to a probability of takotsubo of 99.4%. The patient's therapy was then optimized with an increase in the dosage of angiotensin receptor antagonists and beta blockers. One month after CAR-T cell infusion, echocardiography showed complete recovery of biventricular function and ECG completely normalized, together with the values of BNP and TnI-hs. Medical treatment was left unmodified. Conclusions: the pathophysiology of left ventricular systolic dysfunction during CAR-T cell therapy is unclear, but the main hypotheses are IL-6 mediated myocardial depression during CRS, stress-induced or takotsubo cardiomyopathy, and direct toxicity from CAR-T cells. From the currently available data from retrospective studies, cardiovascular events strongly overlap with CRS and, particularly, with high-grade CRS. Therefore, there is a strong rationale for early treatment with tocilizumab as it has been postulated from retrospective data a lower risk of cardiovascular events with earlier administration of tocilizumab during CRS. Surveillance for cardiotoxicity in patients receiving CAR-T cell therapy is mandatory for prompt recognition and treatment of cardiovascular complications. Our understanding of CAR-T cell-induced cardiomyopathy is still limited, and data regarding predictive factors for persistent cardiac dysfunction are lacking. It is important to differentiate cardiovascular events related to CAR-T cell therapy from epiphenomenon of CRS and capillary leak, to allow for a broader assessment of cardiac events among future CAR T-cell trials.